2005
DOI: 10.1002/marc.200500274
|View full text |Cite
|
Sign up to set email alerts
|

Wettability of Polyhedral Oligomeric Silsesquioxane Nanostructured Polymer Surfaces

Abstract: Summary: Some model structures of waterborne polyurethane anionomers containing various amounts (ca. 3–20%) of a diol functionalized polyhedral oligomeric silsesquioxane (POSS) nanofiller were prepared. X‐ray diffraction showed the formation of a nanocrystalline structure in all copolymers considered. Static contact angle measurements indicated a significant enhancement of surface hydrophobicity as well as reduction in surface tension components even at the least POSS level (3%). Dynamic contact angle cycles a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 19 publications
4
48
0
Order By: Relevance
“…These findings are consistent with previously reported studies showing increased surface hydrophobicity for other POSS/polymer systems and POSS molecules with fluorinated alkyl chains attached to the POSS cage. 12,[21][22][23][24] Surface dynamics were further studied via dynamic water contact angle analysis. The advancing (h a ) and receding (h r ) water contact angles were measured and their difference, the contact angle hysteresis (h h ), was calculated (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with previously reported studies showing increased surface hydrophobicity for other POSS/polymer systems and POSS molecules with fluorinated alkyl chains attached to the POSS cage. 12,[21][22][23][24] Surface dynamics were further studied via dynamic water contact angle analysis. The advancing (h a ) and receding (h r ) water contact angles were measured and their difference, the contact angle hysteresis (h h ), was calculated (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reveal non-homogenously dispersed POSS crystalline aggregates ranging from a few hundred nanometers to several microns. 6,18 Recently, studies on surface properties of POSS HPNC's have appeared in the literature, and these are focused mainly on the surface hydrophobicity of POSS based copolymers, 21,22 fluorinated POSS, 23 and fluorinated POSS/ fluorinated polymer composites. 24 All of these studies report increased hydrophobicity on incorporation of POSS nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In most of the cases the polar component's value was higher than the dispersive one's indicating that the dipolar forces and the hydrogen bonds played an important role in the structure of the polyurethanes and polyurethane networks. The value of the molar free energy of hysteresis was higher in ethylene glycol than that in water, in most of the cases, suggesting that the contribution of dipolar forces and hydrogen bonds in water was more pregnant in ethylene glycol [48].…”
Section: Surface Characterization Of the Networkmentioning
confidence: 86%
“…In this series, POSS particles with different number and configuration of functional groups were used leading to a plurality of chain architectures. Turri et al [47,48] synthesized a linear ionomeric PU/ POSS nanocomposite through a diol-functionalized POSS macromer. More recently Huang et al [49,50] reported on systems based on natural resources, i.e., castor oil and soycastor oil, combined with isophorone diisocyanate and a double-decker POSS moiety.…”
Section: Polyurethane/poss Nanocompositessynthesis and Processingmentioning
confidence: 99%